Anais Do XXXI Simpósio Brasileiro De Informática Na Educação (SBIE 2020) 2020
DOI: 10.5753/cbie.sbie.2020.1102
|View full text |Cite
|
Sign up to set email alerts
|

Mineração de Dados Educacionais na Previsão de Evasão: uma RSL sob a Perspectiva do Congresso Brasileiro de Informática na Educação

Abstract: Este trabalho apresenta uma revisão sistemática de estudos que utilizam técnicas de mineração de dados educacionais no contexto da previsão de evasão estudantil e que foram publicados no Congresso Brasileiro de Informática na Educação, principal evento da área no país. Características contextuais (redes, modalidades e níveis de ensino), técnicas (tarefas, categorias de algoritmos e ferramentas) e de dados (tipos, abrangência e volume) foram analisadas com o intuito de identificar como esse tema está sendo abor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
5
0
7
Order By: Relevance
“…The difficulty in accessing remote classes, for example, possibly due to a lack of technological resources, has been one of the main causes of the growing student dropout rate, according to a study by Datafolha Institute (Saldaña, 2021). Thus, student dropout, defined by the Brazilian Ministry of Education as the definitive departure of the student from his academic programme/degree of origin without completing it (Brazil, 1997), which already represented a problem to be combated by the educational system (Colpo et al, 2020), has caused even greater concern during the pandemic. It is important to highlight that, besides social and academic damage, the dropout harms the country's economic development, given the correlation between the level of schooling and the population's wage gains (Pontili et al, 2018).…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in accessing remote classes, for example, possibly due to a lack of technological resources, has been one of the main causes of the growing student dropout rate, according to a study by Datafolha Institute (Saldaña, 2021). Thus, student dropout, defined by the Brazilian Ministry of Education as the definitive departure of the student from his academic programme/degree of origin without completing it (Brazil, 1997), which already represented a problem to be combated by the educational system (Colpo et al, 2020), has caused even greater concern during the pandemic. It is important to highlight that, besides social and academic damage, the dropout harms the country's economic development, given the correlation between the level of schooling and the population's wage gains (Pontili et al, 2018).…”
Section: What This Paper Addsmentioning
confidence: 99%
“…The academic model, which before the pandemic outperformed the economic and interactional models, no longer significantly outperforms the interactional model. Colpo et al (2020) identified that research on dropout prediction typically focuses on academic and demographic/social data in face-to-face education, and on academic and interactional data in distance education. This trend may be a reflection of the predictive potential of these types of data in these modalities of education.…”
Section: Predictive Performancementioning
confidence: 99%
“…Nesse contexto, o trabalho de [Colpo et al 2020] realizou uma RSL com a meta de analisar estudos publicados nos anais do Congresso Brasileiro de Informática na Educac ¸ão (CBIE) no período de 2006 a 2019, sobre o uso das técnicas de EDM na previsão da evasão do estudante em todas as fases de ensino. Ao final, 23 estudos foram selecionados e analisados e, dentre os resultados, apresentaram a falta de envolvimento dos profissionais na busca de soluc ¸ões contra a evasão escolar.…”
Section: Trabalhos Relacionadosunclassified
“…Há estudos que analisam técnicas e métodos aplicados na predição de evasão, sem buscar uma compreensão de como os indicadores orientam a construção dos modelos preditivos (MASCHIO et al, 2018;MARQUES et al, 2019;COLPO et al, 2020). Os estudos de Maschio et al (2018), Marques et al (2019), Mduma, Kalegele and Machuve (2019), Will, Kemczinski and Parpinelli (2019), Colpo et al (2020) concentraram-se em revisar aspectos técnicos (i.e., métodos, algoritmos e ferramentas), resultados e aplicaç ões de Mineração de Dados Educacional (MDE), não se preocuparam portanto em analisar também a influência dos indicadores na seleção dos métodos ou algoritmos (uma das etapas da construção dos modelos preditivos). Os estudos secundários feitos até aqui não têm exteriorizado como os indicadores são abordados na construção dos modelos.…”
Section: Introduç˜ Aounclassified